Compromised longevity due to Mycobacterium abscessus pulmonary disease in lungs scarred by tuberculosis. Issue 3 (20th March 2019) - Singh, Urvashi B.; Das, Rojaleen; Shrestha, Prajowl; Bala, Kiran; Pandey, Pooja; Verma, Santosh Kumar; Gautam, Hitender; Story-Roller, Elizabeth; Lamichhane, Gyanu; Guleria, Randeep
Abstract : Structural lung diseases or scarring related to prior infections such as tuberculosis (TB) are risk factors for the development of invasive nontuberculous mycobacterial (NTM) pulmonary infections, such as Mycobacterium abscessus .M. abscessus is intrinsically resistant to many antibiotics and in vitro susceptibility correlates poorly with clinical response, especially in pulmonary disease. Treatment is often difﬁcult due to the lack of effective antibiotic regimens. We present a case of a 56-year-old male previously treated for TB, with presumed exacerbation, who was diagnosed after much delay with pulmonary M. abscessus disease and subsequently failed initial treatment with an empirical antibiotic regimen. When placed on a synergistic combination regimen that included amikacin, linezolid, clarithromycin, ethambutol and faropenem, the patient showed a favourable response and was culture-negative for over 12 months when the treatment was stopped as per American Thoracic Society (ATS) recommendations. Unfortunately, he developed recurrent symptoms and died 9 months after stopping treatment, following an acute exacerbation of fever and respiratory failure.